How to Use Emerging Service Technologies to Enhance Customer Centricity in Business-to-Business Contexts: A Conceptual Framework and Research Agenda - Wünderlich, Nancy; Blut, Markus; Brock, Christian; Heirati, Nima; Jensen, Marcus; Paluch, Stefanie; Rötzmeier-Keuper, Julia; Tóth, Zsófia (Journal of Business Research, 2025)
Manufacturers in business-to-business (B2B) industries aim to gain a competitive edge by adopting the concept of customer centricity in their strategy. Acknowledging manufacturers’ challenges in implementing new technologies, we showcase how digital product passports, augmented/virtual reality, smart products, and digital twins foster customer centricity. We classify these technologies based on their use context and introduce the CCTECH-framework, which delineates the impact of (1) experiential, (2) performance-enhancing, and (3) automated technologies on customer-centric processes. This research explores the opportunities for utilizing specific emerging technologies to enhance four customer-centric processes: (1) interactive customer relationship management (discovering implicit needs), (2) customer integration (systematic involvement of customers in decision-making), (3) internal integration (aligning business activities around customer value), and (4) external integration (supply chain-level coordination to respond to customization required by customers). Further, we provide a technology roadmap for manufacturers and suggest a research agenda to guide future research.
Keywords: B2BManufacturing; Customer centricity; Emerging technology; Service technology